2019
DOI: 10.1080/00131911.2019.1566208
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulated learning in MOOCs: lessons learned from a literature review

Abstract: Self-regulated learning in MOOCs: Lessons learned from a literature reviewLearners in Massive Open Online Courses (MOOCs) are required to be autonomous during their learning process, and thus, they need to self-regulate their learning to achieve their goals. According to existing literature, Selfregulated learning (SRL) research in MOOCs is still scarce. More studies which build on past works regarding SRL in MOOCs are required, as well as literature reviews that help to identify the main challenges and future… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(43 citation statements)
references
References 58 publications
(102 reference statements)
2
36
0
5
Order By: Relevance
“…In short, they study how to be able to carry out and finish a MOOC in a satisfactory way without having a sequential learning progress. This finding made by Alonso Mencía et al [44], [48], can be used effectively in the creation of MOOCs considering a diversity of activities, tasks and means, providing the possibility that students can build their own way of learning.…”
Section: Rq8) How Can Self-regulation Learning and Its Strategies Sumentioning
confidence: 94%
See 1 more Smart Citation
“…In short, they study how to be able to carry out and finish a MOOC in a satisfactory way without having a sequential learning progress. This finding made by Alonso Mencía et al [44], [48], can be used effectively in the creation of MOOCs considering a diversity of activities, tasks and means, providing the possibility that students can build their own way of learning.…”
Section: Rq8) How Can Self-regulation Learning and Its Strategies Sumentioning
confidence: 94%
“…To date, different literature reviews have been developed in the field of self-regulated learning in MOOCs for various purposes. The review carried out by Alonso et al [48] states that research in MOOCs and its relationship with selfregulated learning is still scarce and there is a tendency not to specify which SRL model is used; This review was carried out from 2008 to 2017 and one of the inclusion criteria is actual experience with at least one MOOC. For their part, Lee et al [17] carried out a literature review from 2008 to 2016 in which they identified SRL strategies as motivational regulation strategies, specifically self-efficacy, task value, and goal setting, and they also concluded that the understanding of self-regulation in MOOCs is still limited.…”
Section: Literature Reviews Concerning Srl In Moocsmentioning
confidence: 99%
“…Selain itu, bisa juga dilakukan sistem pendeteksian dini (intervensi pada mahasiswa). Lebih lanjut lagi, sistem pendeteksian dini dapat digabungkan dengan metodologi Self-Regulated Learning (SRL) [26], tergantung pada tingkat kategori risiko dari mahasiswa, yaitu dengan memberikan suatu tindakan akademis terhadap mahasiswamahasiswa yang berisiko tinggi, baik dengan komunikasi langsung meningkatkan keterlibatan dalam suatu kelas tertentu atau dengan cara yang lainnya sesuai risiko dan budaya pada suatu institusi tertentu.…”
Section: B Mitigasi Pembelajaranunclassified
“…Online learning opens the door to lifelong learners, who tend to use online learning to satisfy personal or professional interests (Alonso-Mencía et al 2019). Home-based e-learning is the epitome of lifelong Learning, which learners experience knowledge acquisition and construction in a personal learning environment.…”
Section: Introductionmentioning
confidence: 99%